Analysis of Language Errors in Speech Texts of Grade VIII Students at SMP Negeri 29 Medan - Rahel July Sihotang; Ita Khairani (Journal of English Language and Education, 2026)
This study aims to identify language errors in speech texts written by eighth-grade students at SMP Negeri 29 Medan. The errors analyzed include morphological and syntactic errors. This study employed a descriptive qualitative method, in which the researcher directly observed the research object and produced data in the form of narrative texts. Data were collected through documentation, reading, and note-taking techniques. The data consisted of 96 speech texts written by students of classes VIII-1, VIII-2, and VIII-3 at SMP Negeri 29 Medan. The data analysis was conducted through three stages: data reduction, data display, and conclusion drawing/verification. The results showed that students made language errors at the morphological level, including affixation, reduplication, and composition errors. In addition, syntactic errors were found in phrases and sentences. The most dominant errors were morphological errors in affixation, with 202 errors or 50.75% of the total 398 language errors identified in the study.